If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -3 = 17 Reorder the terms: -3 + 7y = 17 Solving -3 + 7y = 17 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7y = 17 + 3 Combine like terms: -3 + 3 = 0 0 + 7y = 17 + 3 7y = 17 + 3 Combine like terms: 17 + 3 = 20 7y = 20 Divide each side by '7'. y = 2.857142857 Simplifying y = 2.857142857
| x^2+kx+8=k | | 5(m+4)-7= | | 5*x^2-x^2=36 | | 2(x^2-192)=0 | | .66d+1=16-d | | 2(x-3)+5=4x+7 | | -(a-4)=6 | | 10(a+1)-14a=9+(4a-1) | | 0=2x^3-6x^2+8x-3 | | -2(4x-9)=-8x+18 | | 7+5y=39+y | | 119+40+4x=180 | | 400-40w=80 | | 125.00+5.75=228.50 | | 9xh=-63 | | 6x-43=65+x | | 4x-15=1x-13 | | 3/2x+6+1/2x=15+x | | 3x+2y-5x+7y= | | -742+524= | | (x+y)*(x-y)=17 | | 4x+5+7x-7=180 | | y=6mx-3b | | 4.9=-9+x | | -.833=x-.333 | | 19=3(-4b-3)+5b | | 8+3x/5=11 | | 2=2-3r-5r | | -1-(1-c)=2c-11 | | w+12=19 | | -12n+16=-8n-4 | | 6x-43=65+2x |